Multi-objective optimization of process conditions in the manufacturing of banana (Musa paradisiaca L.) starch/natural rubber films - Ramírez Hernández, Aurelio; Aparicio Saguilan, Alejandro; Reynoso-Meza, G.; Carrillo Ahumada, Jesús (Carbohydrate Polymers, 2016)
Multi-objective optimization was used to evaluate the effect of adding banana (Musa paradisiaca L.) starch and natural rubber (cis-1,4-poliisopreno) at different ratios (1–13 w/w) to the manufacturing process of biodegradable films, specifically the effect on the biodegradability, crystallinity and moisture of the films. A structural characterization of the films was performed by X-ray diffraction, Fourier transform infrared spectroscopy and SEM, moisture and biodegradability properties were studied. The models obtained showed that degradability vs. moisture tend to be inversely proportional and crystallinity vs. degradability tend to be directly proportional. With respect to crystallinity vs. moisture behavior, it is observed that crystallinity remains constant when moisture values remain between 27 and 41%. Beyond this value there is an exponential increase in crystallinity. These results allow for predictions on the mechanical behavior that can occur in starch/rubber films.
Keywords: Película; Caucho natural; Almidón de plátano